Light-front zero-mode contribution to the Ward Identity - Sales, J. H. O.; Suzuki, Alfredo Takashi [UNESP] (Elsevier B.V., 2010)
In a covariant gauge we implicitly assume that the Green's function propagates information from one point of the space-time to another, so that the Green's function is responsible for the dynamics of the relativistic particle. In the light front form one would naively expect, that this feature would be preserved. In this manner, the fermionic field propagator can be split into a propagating piece and a non-propagating (contact) term. Since the latter (contact) one does not propagate information; and therefore, supposedly can be discarded with no harm to the field dynamics we wanted to know what would be the impact of dropping it off. To do that, we investigated its role in the Ward identity in the light front. Here we use the terminology Ward identity to identify the limiting case of photon's zero momentum transfer in the vertex from the more general Ward-Takahashi identity with nonzero momentum transfer.